Stout, Rawls, and the Idea of Public Reason - Ryan, Phil (Journal of religious ethics, 2014)
Jeffrey Stout claims that John Rawls's idea of public reason (IPR) has contributed to a Christian backlash against liberalism. This essay argues that those whom Stout calls “antiliberal traditionalists” have misunderstood Rawls in important ways, and goes on to consider Stout's own critiques of the IPR. While Rawls's idea is often interpreted as a blanket prohibition on religious reasoning outside church and home, the essay will show that the very viability of the IPR depends upon a rich culture of deliberation in which all forms of reasoning can be put forth for consideration. This clarification addresses the perception that the IPR imposes an “asymmetrical burden” upon believers. In fact, the essay suggests that there are good reasons why believers, qua believers, might endorse the IPR.